Manajemen Kearsipan untuk Tertib Administrasi di Kantor Kecamatan Salahutu, Kabupaten Maluku Tengah - Sahetapy, Petronela (Penerbit Goodwood, 2025)
Purpose: The purpose of this community service program is to improve the understanding and skills of employees in organizing archives to support administrative order, thereby enhancing the efficiency and effectiveness of organizational work. Methodology: The activity was carried out at the District Office of Salahutu, involving employees as participants. The approach used was an interactive lecture method, combining theoretical explanation with direct practice. Participants learned about the importance of archives, mail management, file formation, archive reduction, and archive preservation. Supporting tools included archive classification forms, filing cabinets, and labeling equipment. Results: The program resulted in increased participants’ knowledge and skills in organizing archives systematically according to established procedures. The District Office adopted a one-gate system for incoming and outgoing mail, developed archive formation guidelines, and began implementing digital archiving. Overall, the activity positively improved the quality of archival management, making the process more structured, systematic, and capable of meeting organizational needs effectively and efficiently. Conclusions: The archival organization program demonstrated a positive impact on employees’ understanding and practical skills. With comprehensive materials, interactive learning, leadership support, and active participation, archive management became more organized, efficient, and aligned with administrative standards. Challenges such as employee resistance and misconceptions were addressed through intensive socialization and technological innovations, including digital archiving. Limitations: This program was only implemented in one location and within a limited timeframe, so its results may not represent other regions with different conditions. Contribution: This program contributes to improving public sector administrative management, particularly in archival practices.